1999
DOI: 10.1089/jop.1999.15.351
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Interleukin-1α-Induced Uveitis and Inhibition of Fibroblast-like Cell Proliferation by Synthetic Interleukin-1 Blockers

Abstract: To treat uveitis and prolong the functional life of filtration surgery on glaucomatous eyes, some interleukin-1 (IL-1) blockers were used to inhibit IL-1-induced uveitis in rat eyes and to suppress proliferation of fibroblast-like corneal and conjunctival cells in the cell cultures, respectively. It was found in this research that the blood-aqueous barrier can be broken by IL-1alpha to allow fluorescein to enter the eyeballs and to be detected by fluorotron. The uveitis was effectively blocked by the IL-1 bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Several studies have also shown that IL-1 is a potent stimulator of fibroblast proliferation (5,(7)(8)(9)26,27), and Inokuchi et al (28) demonstrated that IL-1α stimulates cell proliferation through Ca 2+ /calmodulindependent pathway in NIM 1 cells, a human thyroid cell line established from a patient with thyroid papillary adenocarcinoma. The findings of recent papers that the IL-1 blockers, CK-119 and CK-122 (29) and 1-methyl hydrazine analogs (30,31) inhibit the cell proliferation in human lung fibroblasts and fibroblast-like cells, respectively, also suggest that IL-1 enhances cell growth in fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also shown that IL-1 is a potent stimulator of fibroblast proliferation (5,(7)(8)(9)26,27), and Inokuchi et al (28) demonstrated that IL-1α stimulates cell proliferation through Ca 2+ /calmodulindependent pathway in NIM 1 cells, a human thyroid cell line established from a patient with thyroid papillary adenocarcinoma. The findings of recent papers that the IL-1 blockers, CK-119 and CK-122 (29) and 1-methyl hydrazine analogs (30,31) inhibit the cell proliferation in human lung fibroblasts and fibroblast-like cells, respectively, also suggest that IL-1 enhances cell growth in fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorotron provides a non‐invasive technique for measuring the fluorescence content along the axes of eye during the time period under study and has been used to evaluate the blood–aqueous barrier (Wu et al. 1995; Chiou et al. 1999; Carmo et al.…”
Section: Discussionmentioning
confidence: 99%
“…To date, numerous synthetic compounds have been found to produce effective inhibitory actions on interleukin-1 (IL-1 )-induced uveitis and corneal fibroblast proliferation (1)(2)(3)(4)(5)(6)(7)(8). Among them, 1-methyl hydrazino derivatives were found to be most potent and promising (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, 1-methyl hydrazino derivatives were found to be most potent and promising (4)(5)(6)(7)(8). They could be used for the treatment/prevention of IL-1 -induced uveitis, scar formation after glaucoma filtration surgery (9,10) and myopia's photorefractive keratectomy (PRK) and laser in situ keratomileusis (LASIK) (8,11,12).…”
Section: Introductionmentioning
confidence: 99%